A evolução da pobreza e da desigualdade brasileiras ao longo da década de 90 (Economia Aplicada, 1999)
This paper describes the evolution of poverty and inequality in Brazil during the 1990s. In particular, it qualifies the effects of the Real plan on social welfare. The main methodological contributions of the paper refers to the use of longitudinal information. First, we present a dynamic comparison of changes of income distribution that allow us to relax the hypothesis of anonimity (or alternatively a constant ranking). Second, the fall of inequality of current monthly income during the post stabilization period overestimates the fall of inequality of permanent income. The difference between these two inequality measures can be explained in terms of the fall ofthe temporal variability of individual income. As its name suggests one key implication of a successful stabilization program is to make actual earnings more stable.